An enhanced non–local failure criterion for laminated glass under low velocity impact. (November 2017) - Alter, Christian; Kolling, Stefan; Schneider, Jens
Highlights: New non-local failure criterion for laminated glass. The model is based on stress-rate-dependent fracture mechanics. A scalar damage model decreases the strength in the direction of a crack. Numerous head impact tests on windscreens were performed to validate the model. Significant improvement of the reliability of head impact simulations. Abstract: An enhanced non-local failure criterion for laminated safety glass under low velocity impact for explicit finite element simulations with element erosion is presented. Hereby, the fracture strength of the glass depends on the stress rate and is approximated by a power law for the crack velocity resulting from the sub–critical crack growth. In dependence of the size of the finite elements, the singularity of the stress field in the vicinity of the crack tip is underestimated by the element erosion technique. In contrast to classical linear elastic fracture mechanics, the model uses a non-local approach for a decrease of strength in the direction of a crack perpendicular to the maximum in–plane stresses, instead of an increase of the stress field in the vicinity of the crack tip. The failure criterion is implemented in the explicit solver LS–DYNA as an user defined material model. In order to investigate the accuracy of the model, the results are compared to head impact tests on windscreens used in the context of crash simulations.